STRATEGI PENDAYAGUNAAN DANA ZAKAT PADA BIDANG PENDIDIKAN MELALUI PROGRAM BEASISWA S1 DI BAZNAS KOTA CIMAHI - Moch Dadi Fitriyadi; Sundari, Asri; Husen, Susgrandini (Pelita Nusa Jurnal, published by the Institute for Research and Community Service (LP2M) of the Pelita Nusa Islamic Religious College West Bandung (STAI PENUS), 2024)
The 2022 Higher Education Statistics Report shows that as many as 601,333 students dropped out of college in 2022. The high rate of college dropouts cannot be balanced with the productive zakat funds in Baznas Cimahi City. This study aims to analyze the strategy of utilizing Zakat funds in the field of education through the S1 Scholarship program held by Baznas Cimahi City, including the planning, obstacles, and effectiveness of the strategy. This study uses a qualitative approach with a descriptive method. Source triangulation techniques are used to verify the validity of the data. The results of the study show that the Cimahi City Baznas implements a strategy for planning, implementing, and evaluating the utilization of zakat funds in the field of education. The obstacles found include inconsistencies in budget realization with planning, lack of implementation schedules, limited facilities, and monitoring that is still carried out simply. However, the effectiveness of this program is considered quite good. This study provides recommendations for the Cimahi City Baznas to improve the strategy of utilizing zakat funds in the education sector to be more effective and reduce the rate of college dropouts.